Belowground biomass and nutrient dynamics in traditional agroforests of northeast India - Deb, S.; Arunachalam, A.; Das, A.K.; Arunachalam, K. (Indian Journal of Agroforestry, 2020)
This paper deals with the importance of roots in nutrient dynamics of traditional agroforests. In order to compare the differential influence of management practices, data on systems practiced by two ethnic communities’ viz., ‘Kalitas’ (Harmutty village, Assam) and ‘Nyishis’ (Nirjuli and Doimukh villages, Arunachal Pradesh) in northeast India have been chosen. Based on the ecology, it is observed that greater concentration of fine roots (< 2 mm diameter) were in the top 0-10 cm soil profile and coarse roots (> 2 mm) in the 20-30 cm depth; that has been attributed to the abundance of multipurpose trees. Indigenous use of cowdung and other biofertilizers by the farmers of Harmutty in traditional agroforests resulted in greater fine root biomass and nutrient accumulation. The fine and coarse root biomass showed significant increase or decrease with the climatic variables like rainfall, humidity, soil temperature and air. A view on biomass turnover of different diameter classes of roots showed that larger diameter (1-2 mm) fine roots have longer mean residence period than the smaller diameter (< 1 mm) fine roots. N accumulation of fine and coarse roots was higher than P accumulation and the rate of N and P accumulation in fine roots decreased with increasing soil depth, due to limited input of organic matter. Nutrient contributions of different components in the belowground production indicated that the fine roots and microbial biomass play a greater role in soil nitrogen and carbon dynamics. Nonetheless, synchronization of microbial activities with the detrital input mechanisms would help in the sustainable nutrient management of the soil in traditional agroforestry systems per se.